Fire-retardant cable and preparation method thereof
By mixing organic composite bentonite with trihydrate oxide to prepare aerogel layer-wrapped cables, the existing flame-retardant wire and cables are easily fused, melted in the insulation layer or burned in high temperature environments, and the fire-retardant effects of the cables are achieved, and the production cost and process complexity are reduced.
Patent Information
- Application Number
- CN202410793431.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-06-19
- Publication Date
- 2025-05-02
- Estimated Expiration
- 2044-06-19
AI Technical Summary
Existing flame-retardant wires and cables are prone to fuse, the insulation layer melts or catches fire and burns in high temperature environments, and the fire resistance is not ideal, and the manufacturing process is complex and the cost is high.
The aerogel layer-wrapped cable is prepared by mixing organic composite bentonite with alumina trihydrate. The interlayer peeling structure is formed by ultrasonic radiation, and the reaction of acrylic acid and phenyl phosphorus dichloride is combined to form an organic phosphorus-based flame retardant compound to form a tight composite bentonite structure to achieve fire-proof and flame retardant effects.
The fire-proof and flame-retardant effect of cables in high temperature environments is achieved, which reduces material and production costs, simplifies processes, and improves the overall performance of cables.
Smart Images

Figure BDA0004900764240000081 
Figure BDA0004900764240000091
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of power transmission and distribution line equipment, in particular to a fire-proof and flame-retardant cable and a preparation method thereof. Background Art
[0002] The current flame-retardant wires and cables only have the function of high-temperature flame retardancy, and cannot prevent fire. Generally, mica tape is only wrapped around the conductor or the insulation layer. When such cables are in a high-temperature environment, although the mica tape is not affected by the high temperature, the conductive conductor inside the mica tape will melt due to the high temperature, resulting in line interruption, and the insulation layer will melt or even catch fire. In addition, the mica tape is easily dragged during the installation of wires and cables, causing mechanical damage, and thus cannot play a role in fire prevention and insulation.
[0003] Existing fireproof cables are either complex in structure, expensive, or have complex manufacturing processes, and have extremely high requirements for installation and laying, while their fireproof performance is not ideal. How to simplify the process and improve the fireproof performance of cables while reducing material and production costs is of great significance. Organic bentonite has many excellent properties, such as good thermal stability, high residual carbon content, large reserves, and low production costs. However, due to its own structure, the interlamellar spacing of bentonite is small and it is easy to agglomerate in the polymer matrix. In addition, the flame retardant effect of bentonite is general and cannot meet the demand for fireproof materials. However, there are a large number of exchangeable cations between bentonite layers, which provides the necessary conditions for modification. The modified organic bentonite is mixed with alumina trihydrate to prepare an aerogel layer as a fire-retardant layer. Based on this idea, the present invention provides a fire-retardant cable and a preparation method thereof. Summary of the invention
[0004] The object of the present invention is to provide a fire-resistant and flame-retardant cable and a preparation method thereof, so as to solve the problems existing in the prior art.
[0005] In order to solve the above technical problems, the present invention provides the following technical solutions: a fire-proof and flame-retardant cable, wherein the cable comprises, from inside to outside, an insulating cable core, a modified aerogel layer, a stainless steel layer, and an outer sheath layer.
[0006] Furthermore, the modified aerogel layer is prepared by mixing organic composite bentonite and alumina trihydrate.
[0007] Furthermore, the organic composite bentonite is prepared by ultrasonically treating bentonite, reacting with rubber and acrylic acid to generate an organic phosphorus flame retardant and polyacrylic acid, and then heating and accumulating the resultant.
[0008] Furthermore, a method for preparing a fire-retardant cable comprises the following preparation steps:
[0009] (1) Mixing organic quaternary ammonium salt intercalated bentonite with deionized water at a mass ratio of 1:1000-5000, oscillating for 10-20 minutes under ultrasonic wave with a frequency of 20kHz-120kHz and a power of 100W-1200W, taking the solid, and drying it at 50°C for 2 hours; heating the high-speed mixer to 180-200°C, keeping the temperature constant for 5-15 minutes, adding 6-10 parts of dried bentonite and 2 parts of butyl rubber, stirring at a speed of 600r / min for 15-25 minutes, continuing to stir and reducing the temperature; The temperature is raised to 110-120°C, 1-5 parts of acrylic acid are added and stirring is continued for 5-15 minutes, then 0.05-0.25 parts of phenylphosphonium dichloride and 0.08-0.2 parts of ammonium persulfate are added and stirring is continued for 20 minutes, and then steaming is performed at a temperature of 80-100°C for 4-6 hours. After steaming, the mixture is put into a glass cup and placed in a heating chamber of a muffle furnace at a heating temperature of 105°C for 1-15 days. After heating, the mixture is cooled to room temperature to prepare an organic composite bentonite.
[0010] (2) Soaking polystyrene with a cross-linking degree of 5-15% in anhydrous ethanol for 24-48 hours, taking it out and air-drying it at room temperature for 6 hours, placing the air-dried polystyrene and tetrabutyl titanate in a mixed solution of dichloromethane and carbon tetrachloride, heating it to 50° C., stirring it at a speed of 200-300 r / min for 12-15 hours, and then lowering the temperature to room temperature to obtain an aerogel precursor;
[0011] (3) using an extruder to extrude the aerogel precursor onto the insulating cable core at an extrusion temperature of 55-65°C, then placing it in a high-pressure sealed device, pressurizing it to 16MPa and heating it to 40-60°C, and maintaining the temperature for 8-10h. After completion, the pressure is reduced and the temperature is reduced to normal pressure and temperature to obtain a polystyrene aerogel layer cable; trihydrate aluminum oxide, organic composite bentonite, polydopamine, vinyl triethoxysilane and benzyl alcohol are uniformly mixed, and then 5mm agate balls are added as ball milling media, and the ball-to-material ratio is 10:1. The ball mill jar is placed in a ball mill and ball milled at a speed of 550r / min for 15-75min to obtain a filler; the filler is evenly sprayed on the surface of the polystyrene aerogel layer cable, and then placed in a sealed environment at 30-40°C for 3-5h, then heated to 70-80°C for 2-3h, and finally heated to 100-120°C for 30-60min to obtain a modified aerogel layer cable;
[0012] (4) The cable core coated with the modified aerogel is coated and welded online with a stainless steel belt, and the stainless steel tube after welding is corrugated; a sheath layer is wrapped outside the stainless steel layer, and its raw materials include the following components by weight: 40-50 parts of chlorosulfonated polyethylene, 15-25 parts of chlorinated polyethylene, 8-16 parts of EVA, 20-30 parts of halogen-free low-smoke flame-retardant polyolefin, 1-2 parts of vinyl triethoxysilane, and 1-2 parts of silane coupling agent KH550.
[0013] Furthermore, in the step (1), the size of the organic bentonite is 20-200 mesh.
[0014] Furthermore, in the step (2), the weight ratio of the air-dried low-crosslinked polystyrene, tetrabutyl titanate, dichloromethane and carbon tetrachloride is 10-16:1:20:50.
[0015] Furthermore, in the step (3), the mass proportions of alumina trihydrate, organic composite bentonite, polydopamine, vinyltriethoxysilane and benzyl alcohol are 10-20 parts, 5-13 parts, 5-11 parts, 2-4 parts and 15-35 parts respectively.
[0016] Furthermore, in step (3), the weight ratio of the filler to the polystyrene aerogel is 0.5-1:1.
[0017] Furthermore, the silane coupling agent in step (4) is silane coupling agent KH550.
[0018] Furthermore, the stainless steel sheath in step (4) is made by welding and corrugating a stainless steel strip with a thickness of 0.1-0.2 mm, a tensile strength of 520-595 MPa, and an elongation of 42%-48%. During welding, a mixed gas of helium and argon with a volume ratio of 1:2 is used for protection. The minimum bending radius of the obtained cable is 7-15 times the diameter of the cable.
[0019] Compared with the prior art, the beneficial effects achieved by the present invention are:
[0020] The invention uses an aerogel layer prepared by mixing organic composite bentonite with inorganic trihydrate alumina to wrap the cable, so as to achieve fireproof and flame retardant effects.
[0021] First, the organic bentonite is subjected to ultrasonic radiation to generate an interlayer peeling structure under the action of high-frequency mechanical waves, and then rubber is inserted into the interlayer structure of the bentonite to form a composite material with a nano-dispersed structure, and acrylic acid is inserted into the gaps of the composite material so that the composite material is infiltrated with acrylic acid to form a loose three-dimensional network structure; after being mixed and added with phenyl phosphorus dichloride, the bentonite is steamed at high temperature, and during the steaming process, part of the acrylic acid reacts with phenyl phosphorus dichloride to generate an organic phosphorus flame retardant compound, and the excess acrylic acid monomer is in-situ addition polymerized to obtain polyacrylic acid, which locks the organic phosphorus flame retardant compound and makes it firmly attached to the three-dimensional structure of the bentonite, captures the free radicals generated by the cracking of silicone rubber during combustion, and inhibits and delays the combustion reaction; and then the bentonite is dried by heating, while the inter-crystalline spacing of the bentonite is reduced, and silicon oxide is generated by itself to cement the remaining mineral components, so that the bentonite undergoes condensation and accumulation behavior, and the structure of the composite bentonite tends to be compact, and the air contact surface is reduced to achieve the flame retardant and fireproof effect;
[0022] Secondly, the treated composite bentonite is mixed with alumina trihydrate and used as a filler to prepare a flame retardant and fireproof aerogel layer. When the temperature of the aerogel layer is too high, the alumina trihydrate will absorb heat and dehydrate, slowing down the rate of temperature rise of the aerogel layer to achieve a flame retardant effect. In addition, the released water will be absorbed by the surrounding composite bentonite. The absorbed and swollen bentonite will wrap and extend due to its volume change, and carbonization will block the contact between the combustible part and the combustion-supporting gas, and the synergistic mechanism with alumina trihydrate will further achieve the flame retardant effect. DETAILED DESCRIPTION
[0023] The following will be combined with the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without making creative work are within the scope of protection of the present invention.
[0024] In order to more clearly illustrate the method provided by the present invention, the following examples are used to describe in detail the various index testing methods of a fire-retardant cable prepared in the following examples.
[0025] Flame retardancy: The sample cables of the embodiment and the comparative example were subjected to flame retardancy test: the sample cables were kept vertical, and the flame height of the test blowtorch was 125mm, the heat power was 500W, and it was burned for 15s, and then stopped for 15s. After repeating 5 times, the residual flame burning time was observed, and the degree of burnt was determined according to the overall appearance after the flame was extinguished. The above experiment tested each cable three times and the average value was taken.
[0026] Oxygen index: the sample cables of the embodiment and the comparative example are tested according to the method in GB / T2406-2008 "Plastic Combustion Performance Test Method Oxygen Index Method"; the corresponding standard value is ≥32 according to the standard in JB / T10707-2007;
[0027] Example 1
[0028] (1) Mix 20-mesh organic quaternary ammonium salt intercalated bentonite with deionized water at a mass ratio of 1:1000, oscillate for 10 minutes under ultrasonic wave with a frequency of 20 kHz and a power of 100 W, take the solid, and dry it at 50° C. for 2 hours; heat the high-speed mixer to 180° C., keep the temperature constant for 5 minutes, add 6 parts of dried bentonite and 2 parts of butyl rubber, stir at a speed of 600 r / min for 15 minutes, continue to stir and cool to 110° C., add 1 part of acrylic acid and continue to stir for 5 minutes, then add 0.05 parts of phenylphosphine dichloride and 0.08 parts of ammonium persulfate, continue to stir for 20 minutes, and then steam cook at a cooking temperature of 80° C. for 4 hours. After the cooking is completed, put it into a glass cup and place it in the heating chamber of a muffle furnace at a heating temperature of 105° C. for 1 day; cool it to room temperature after heating to prepare an organic composite bentonite;
[0029] (2) Soaking polystyrene with a cross-linking degree of 5% in anhydrous ethanol for 24 hours, taking it out and air-drying it at room temperature for 6 hours, placing the air-dried polystyrene and tetrabutyl titanate in a mixed solution of dichloromethane and carbon tetrachloride, wherein the weight ratio of the air-dried low cross-linking degree polystyrene, tetrabutyl titanate, dichloromethane and carbon tetrachloride is 10:1:20:50; heating the mixed solution to 50° C., stirring at a speed of 200 r / min for 12 hours, and then lowering the temperature to room temperature to obtain an aerogel precursor;
[0030] (3) The aerogel precursor is extruded onto the insulating cable core by an extruder at an extrusion temperature of 55°C, and then placed in a high-pressure sealed device, pressurized to 16MPa and heated to 40°C, and the temperature is maintained for 8h. After completion, the pressure is reduced and the temperature is cooled to normal pressure and temperature to obtain a polystyrene aerogel layer cable; trihydrate aluminum oxide, organic composite bentonite, polydopamine, vinyl triethoxysilane and benzyl alcohol are mixed in 10 parts, 5 parts, 5 parts, 2 parts and 15 parts by weight, and then 5mm agate balls are added as ball milling media with a ball-to-material ratio of 10:1. The ball mill jar is placed in a ball mill and ball milled at a speed of 550r / min for 15min to obtain a filler; the filler is evenly sprayed on the surface of the polystyrene aerogel layer cable, and then placed in a sealed environment at 30°C for 3h, then heated to 70°C for 2h, and finally heated to 100°C for 30min to obtain a modified aerogel layer cable;
[0031] (4) The cable core coated with modified aerogel is coated and welded online with a stainless steel strip, and the stainless steel tube after welding is corrugated; the stainless steel sheath is made by welding and corrugating a stainless steel strip with a thickness of 0.1 mm, a tensile strength of 520 MPa, and an elongation of 42%; during welding, a mixed gas of helium and argon with a volume ratio of 1:2 is used for protection; the minimum bending radius of the obtained cable is 7 times the diameter of the cable; a sheath layer is wrapped around the stainless steel layer, and its raw materials include the following components by weight: 40 parts of chlorosulfonated polyethylene, 15 parts of chlorinated polyethylene, 8 parts of EVA, 20 parts of halogen-free low-smoke flame-retardant polyolefin, 1 part of vinyl triethoxysilane, and 1 part of silane coupling agent KH550.
[0032] Example 2
[0033] (1) Mixing 110 mesh organic quaternary ammonium salt intercalated bentonite with deionized water at a mass ratio of 1:3000, oscillating for 15 minutes under ultrasonic wave with a frequency of 70kHz and a power of 650W, taking the solid, and drying it at 50°C for 2 hours; heating the high-speed mixer to 190°C, keeping the temperature constant for 10 minutes, adding 8 parts of dried bentonite and 2 parts of butyl rubber, stirring at a speed of 600r / min for 20 minutes, continuing to stir and cooling to 115°C, adding 3 parts of acrylic acid and continuing to stir for 10 minutes, then adding 0.15 parts of phenylphosphine dichloride and 0.14 parts of ammonium persulfate, continuing to stir for 20 minutes, and then steaming at a steaming temperature of 90°C for a steaming time of 5 hours. After the steaming is completed, the solid is put into a glass cup and placed in a muffle furnace heating chamber at a heating temperature of 105°C for a heating time of 8 days; cooling to room temperature after heating to prepare an organic composite bentonite;
[0034] (2) Soaking polystyrene with a cross-linking degree of 10% in anhydrous ethanol for 36 hours, taking it out and air-drying it at room temperature for 6 hours, placing the air-dried polystyrene and tetrabutyl titanate in a mixed solution of dichloromethane and carbon tetrachloride, wherein the weight ratio of the air-dried low cross-linking polystyrene, tetrabutyl titanate, dichloromethane and carbon tetrachloride is 13:1:20:50; heating the mixed solution to 50° C., stirring it at 250 r / min for 13.5 hours, and then lowering the temperature to room temperature to obtain an aerogel precursor;
[0035] (3) The aerogel precursor is extruded onto the insulating cable core by an extruder at an extrusion temperature of 60°C, and then placed in a high-pressure sealed device, pressurized to 16MPa and heated to 50°C, and the temperature is maintained for 9 hours. After completion, the pressure is reduced and the temperature is cooled to normal pressure and temperature to obtain a polystyrene aerogel layer cable; trihydrate aluminum oxide, organic composite bentonite, polydopamine, vinyl triethoxysilane and benzyl alcohol are mixed in 15 parts, 9 parts, 8 parts, 3 parts and 25 parts by weight, and then 5mm agate balls are added as ball milling media with a ball-to-material ratio of 10:1. The ball mill jar is placed in a ball mill and ball milled at a speed of 550r / min for 45 minutes to obtain a filler; the filler is evenly sprayed on the surface of the polystyrene aerogel layer cable, and then placed in a sealed environment at 35°C for 4 hours, then heated to 75°C for 2.5 hours, and finally heated to 110°C for 45 minutes to obtain a modified aerogel layer cable;
[0036] (4) The cable core coated with modified aerogel is coated and welded online with a stainless steel strip, and the stainless steel tube after welding is corrugated; the stainless steel sheath is welded and corrugated with a stainless steel strip having a thickness of 0.15 mm, a tensile strength of 560 MPa, and an elongation of 45%; during welding, a mixed gas of helium and argon with a volume ratio of 1:2 is used for protection; the minimum bending radius of the obtained cable is 11 times the diameter of the cable; a sheath layer is wrapped around the stainless steel layer, and its raw materials include the following components in parts by weight: 45 parts of chlorosulfonated polyethylene, 20 parts of chlorinated polyethylene, 12 parts of EVA, 25 parts of halogen-free low-smoke flame-retardant polyolefin, 1.5 parts of vinyl triethoxysilane, and 1.5 parts of silane coupling agent KH550.
[0037] Example 3
[0038] (1) Mixing 200-mesh organic quaternary ammonium salt intercalated bentonite with deionized water at a mass ratio of 1:5000, oscillating for 20 minutes under ultrasonic waves at a frequency of 120 kHz and a power of 1200 W, taking the solid, and drying it at 50° C. for 2 hours; heating the high-speed mixer to 200° C., keeping the temperature constant for 15 minutes, adding 10 parts of dried bentonite and 2 parts of butyl rubber, stirring at a speed of 600 r / min for 25 minutes, continuing to stir and cooling to 120° C., adding 5 parts of acrylic acid and continuing to stir for 15 minutes, then adding 0.25 parts of phenylphosphine dichloride and 0.2 parts of ammonium persulfate, continuing to stir for 20 minutes, and then steaming the mixture at a steaming temperature of 100° C. for 6 hours. After the steaming is completed, the mixture is put into a glass cup and placed in a muffle furnace heating chamber at a heating temperature of 105° C. for 15 days; cooling to room temperature after heating, and preparing an organic composite bentonite;
[0039] (2) Soaking polystyrene with a cross-linking degree of 15% in anhydrous ethanol for 48 hours, taking it out and air-drying it at room temperature for 6 hours, placing the air-dried polystyrene and tetrabutyl titanate in a mixed solution of dichloromethane and carbon tetrachloride, wherein the weight ratio of the air-dried low cross-linking degree polystyrene, tetrabutyl titanate, dichloromethane and carbon tetrachloride is 16:1:20:50; heating the mixed solution to 50° C., stirring at 300 r / min for 15 hours, and then lowering the temperature to room temperature to obtain an aerogel precursor;
[0040] (3) using an extruder to extrude the aerogel precursor onto the insulating cable core at an extrusion temperature of 65°C, then placing it in a high-pressure sealed device, pressurizing it to 16MPa and heating it to 60°C, and maintaining the temperature for 10 hours. After completion, the pressure is reduced and the temperature is reduced to normal pressure and temperature to obtain a polystyrene aerogel layer cable; trihydrate aluminum oxide, organic composite bentonite, polydopamine, vinyl triethoxysilane and benzyl alcohol are mixed in 20 parts, 13 parts, 11 parts, 4 parts and 35 parts by weight, and then 5mm agate balls are added as ball milling media with a ball-to-material ratio of 10:1. The ball mill jar is placed in a ball mill and ball milled at a speed of 550r / min for 75 minutes to obtain a filler; the filler is evenly sprayed on the surface of the polystyrene aerogel layer cable, and then placed in a sealed environment at 40°C for 5 hours, then heated to 80°C for 3 hours, and finally heated to 120°C for 60 minutes to obtain a modified aerogel layer cable;
[0041] (4) The cable core coated with modified aerogel is coated and welded online with a stainless steel strip, and the stainless steel tube after welding is corrugated; the stainless steel sheath is welded and corrugated with a stainless steel strip having a thickness of 0.2 mm, a tensile strength of 595 MPa, and an elongation of 48%; during welding, a mixed gas of helium and argon with a volume ratio of 1:2 is used for protection; the minimum bending radius of the obtained cable is 15 times the diameter of the cable; a sheath layer is wrapped around the stainless steel layer, and its raw materials include the following components in parts by weight: 50 parts of chlorosulfonated polyethylene, 25 parts of chlorinated polyethylene, 16 parts of EVA, 30 parts of halogen-free low-smoke flame-retardant polyolefin, 2 parts of vinyl triethoxysilane, and 2 parts of silane coupling agent KH550.
[0042] Comparative Example 1
[0043] The difference between Comparative Example 1 and Example 2 is that step (1) is different. Step (1) is changed to: 110 mesh organic quaternary ammonium salt intercalated bentonite and deionized water are mixed at a mass ratio of 1:3000, and oscillated for 15 minutes under ultrasonic waves with a frequency of 70kHz and a power of 650W, and the solid is taken and dried at 50°C for 2 hours; the high-speed mixer is heated to 190°C and kept at a constant temperature for 10 minutes, 8 parts of dried bentonite and 3 parts of acrylic acid are added, and stirred at a speed of 600r / min for 20 minutes, and the stirring is continued and the temperature is lowered to 115°C, and then 0.15 parts of phenylphosphonium dichloride and 0.14 parts of ammonium persulfate are added, and the stirring is continued for 20 minutes, and then steam cooking is carried out at a cooking temperature of 90°C and a cooking time of 5 hours. After the cooking is completed, the mixture is put into a glass cup and placed in a muffle furnace heating chamber at a heating temperature of 105°C and a heating time of 8 days; after heating, the mixture is cooled to room temperature to prepare an organic composite bentonite; and the remaining steps are the same as those in Example 2.
[0044] Comparative Example 2
[0045] The difference between Comparative Example 2 and Example 2 is that step (1) is different. Step (1) is changed to: 110 mesh organic quaternary ammonium salt intercalated bentonite and deionized water are mixed at a mass ratio of 1:3000, and oscillated for 15 minutes under ultrasonic waves with a frequency of 70kHz and a power of 650W, and the solid is taken and dried at 50°C for 2 hours; the high-speed mixer is heated to 190°C and kept at a constant temperature for 10 minutes, 8 parts of dried bentonite and 2 parts of butyl rubber are added, and stirred at a speed of 600r / min for 20 minutes, and the stirring is continued and the temperature is lowered to 115°C, 3 parts of acrylic acid are added and stirred for 10 minutes, and then 0.15 parts of phenylphosphonium dichloride are added and stirred for 20 minutes, and then steam cooking is carried out at a cooking temperature of 90°C and a cooking time of 5 hours. After the cooking is completed, the mixture is put into a glass cup and placed in a muffle furnace heating chamber at a heating temperature of 105°C and a heating time of 8 days; after heating, the mixture is cooled to room temperature to prepare an organic composite bentonite; and the remaining steps are the same as those in Example 2.
[0046] Comparative Example 3
[0047] The difference between Comparative Example 3 and Example 2 is that step (1) is different. Step (1) is changed to: 110 mesh organic quaternary ammonium salt intercalated bentonite and deionized water are mixed at a mass ratio of 1:3000, and oscillated for 15 minutes under ultrasonic waves with a frequency of 70kHz and a power of 650W, and the solid is taken and dried at 50°C for 2 hours; the high-speed mixer is heated to 190°C and kept at a constant temperature for 10 minutes, 8 parts of dried bentonite and 2 parts of butyl rubber are added, and stirred at a speed of 600r / min for 20 minutes, and the stirring is continued and the temperature is lowered to 115°C, 3 parts of acrylic acid are added and stirred for 10 minutes, and then 0.14 parts of ammonium persulfate are added and stirred for 20 minutes, and then steam cooking is carried out at a cooking temperature of 90°C and a cooking time of 5 hours. After the cooking is completed, the mixture is put into a glass cup and placed in a muffle furnace heating chamber at a heating temperature of 105°C and a heating time of 8 days; after heating, the mixture is cooled to room temperature to prepare an organic composite bentonite; and the remaining steps are the same as those in Example 2.
[0048] Comparative Example 4
[0049] The difference between Comparative Example 4 and Example 2 is that step (1) is different. Step (1) is changed to: 110 mesh organic quaternary ammonium salt intercalated bentonite and deionized water are mixed at a mass ratio of 1:3000, and oscillated for 15 minutes under ultrasonic waves with a frequency of 70kHz and a power of 650W, and the solid is taken and dried at 50°C for 2 hours; the high-speed mixer is heated to 190°C and kept at a constant temperature for 10 minutes, 8 parts of dried bentonite and 2 parts of butyl rubber are added, and stirred at a speed of 600r / min for 20 minutes, and the stirring is continued and the temperature is lowered to 115°C, 3 parts of acrylic acid are added and stirred for 10 minutes, and then 0.15 parts of phenylphosphonium dichloride and 0.14 parts of ammonium persulfate are added and stirred for 20 minutes, and then steam cooking is carried out at a cooking temperature of 90°C and a cooking time of 5 hours. After the cooking is completed, the mixture is placed in a constant temperature drying oven and dried at 50°C for 5 hours to prepare an organic composite bentonite; the remaining steps are the same as those in Example 2.
[0050] Comparative Example 5
[0051] The difference between Comparative Example 5 and Example 2 is that step (3) is different. Step (3) is changed to: using an extruder to extrude the aerogel precursor onto the insulating cable core, the extrusion temperature is 60°C, and then placing it in a high-pressure sealed device, pressurizing it to 16MPa and heating it to 50°C, and maintaining the temperature for 9h. After completion, the pressure is reduced and the temperature is reduced to normal pressure and temperature to obtain a polystyrene aerogel layer cable; the organic composite bentonite, polydopamine, vinyl triethoxysilane and benzyl alcohol are mixed in 15 parts, 9 parts and 8 parts by mass. , 3 parts and 25 parts are mixed, and then 5 mm agate balls are added as ball milling media with a ball-to-material ratio of 10:1, and the ball mill jar is placed in a ball mill and ball milled at a speed of 550 r / min for 45 min to obtain a filler; the filler is evenly sprayed on the surface of the polystyrene aerogel layer cable, and then placed in a closed environment at 35° C. for 4 h, then heated to 75° C. for 2.5 h, and finally heated to 110° C. for 45 min to obtain a modified aerogel layer cable; and the remaining steps are the same as those in Example 2.
[0052] Effect example
[0053] Table 1 below shows the performance analysis results of a fire-resistant and flame-retardant cable using Examples 1 to 3 of the present invention and Comparative Examples 1 to 5.
[0054] Table 1
[0055]
[0056]
[0057] From the comparison of the experimental data of flame retardancy and oxygen index of the embodiment and the comparative example, it can be found that the present invention subjects the organic bentonite to ultrasonic radiation, generates an interlayer peeling structure under the action of high-frequency mechanical waves, and then inserts rubber into the interlayer structure of the bentonite to form a composite material with a nano-dispersed structure, and inserts acrylic acid in the gaps of the composite material so that the composite material is infiltrated with acrylic acid to form a loose three-dimensional network structure; after mixing and adding phenyl phosphorus dichloride, the bentonite is subjected to high-temperature steam cooking, and during the cooking process, part of the acrylic acid reacts with phenyl phosphorus dichloride to generate an organic phosphorus flame retardant compound, and the excess acrylic acid monomer is in-situ addition polymerized to obtain polyacrylic acid, which locks the organic phosphorus flame retardant compound and makes it firmly adhere to the three-dimensional structure of the bentonite, captures the free radicals generated by the cracking of the silicone rubber during combustion, and suppresses the combustion reaction and Delay; while drying the bentonite by heating, the interplanar spacing of the bentonite is reduced, and silicon oxide is generated by itself to cement the remaining mineral components, so that the bentonite undergoes condensation and accumulation behavior, and the structure of the composite bentonite tends to be compact, reducing the air contact surface to achieve the effect of flame retardancy and fire prevention; the present invention uses the treated composite bentonite mixed with alumina trihydrate as a filler to prepare a flame retardant and fireproof aerogel layer. When the temperature of the aerogel layer is too high, alumina trihydrate will absorb heat and dehydrate, slowing down the rate of temperature rise of the aerogel layer to achieve the effect of flame retardancy. In addition, the released moisture will be absorbed by the surrounding composite bentonite, and the absorbed and swollen bentonite will cover and extend due to its volume change, and carbonization will block the contact between the combustible part and the combustion-supporting gas. The aerogel prepared in this way makes the cable have the effect of fire retardancy and flame retardancy.
[0058] It will be apparent to those skilled in the art that the invention is not limited to the details of the exemplary embodiments described above and that the invention can be implemented in other specific forms without departing from the spirit or essential features of the invention. Therefore, the embodiments should be considered in all respects as exemplary and non-limiting, and the scope of the invention is defined by the appended claims rather than the foregoing description, and it is intended that all variations within the meaning and scope of the equivalent elements of the claims be included in the invention. Any marking in a claim should not be considered as limiting the claim to which it relates.
Claims
1. A fire-retardant cable, which comprises, from inside to outside, an insulating cable core, a modified aerogel layer, a stainless steel layer, and an outer sheath layer, characterized in that: The method comprises the following preparation steps: (1) Mix the organic quaternary ammonium salt intercalated bentonite with deionized water at a mass ratio of 1:1000-5000, oscillate for 10-20 minutes under ultrasonic waves at a frequency of 20kHz-120kHz and a power of 100W-1200W, take the solid, and dry it at 50°C for 2 hours; heat the high-speed mixer to 180-200°C, keep the temperature constant for 5-15 minutes, add 6-10 parts of dried bentonite and 2 parts of butyl rubber, stir at a speed of 600r / min for 15-25 minutes, continue stirring and reduce the temperature; The temperature is raised to 110-120°C, 1-5 parts of acrylic acid are added and stirring is continued for 5-15 minutes, then 0.05-0.25 parts of phenylphosphonium dichloride and 0.08-0.2 parts of ammonium persulfate are added and stirring is continued for 20 minutes, and then steaming is performed at a temperature of 80-100°C for 4-6 hours. After steaming, the mixture is put into a glass cup and placed in a heating chamber of a muffle furnace at a heating temperature of 105°C for 1-15 days. After heating, the mixture is cooled to room temperature to prepare an organic composite bentonite. (2) Soaking polystyrene with a cross-linking degree of 5-15% in anhydrous ethanol for 24-48 hours, taking it out and air-drying it at room temperature for 6 hours, placing the air-dried polystyrene and tetrabutyl titanate in a mixed solution of dichloromethane and carbon tetrachloride, heating it to 50°C, stirring it at a speed of 200-300 r / min for 12-15 hours, and then lowering the temperature to room temperature to obtain an aerogel precursor; (3) The aerogel precursor is extruded onto the insulating cable core by an extruder at an extrusion temperature of 55-65°C, and then placed in a high-pressure sealed device, pressurized to 16MPa and heated to 40-60°C, and the temperature is maintained for 8-10h. After completion, the pressure is reduced and the temperature is cooled to normal pressure and temperature to obtain a polystyrene aerogel layer cable; trihydrate aluminum oxide, organic composite bentonite, polydopamine, vinyl triethoxysilane and benzyl alcohol are uniformly mixed, and then 5mm agate balls are added as ball milling media, and the ball-to-material ratio is 10:
1. The ball mill jar is placed in a ball mill and ball milled at a speed of 550 r / min for 15-75 min to obtain a filler; the filler is uniformly sprayed on the surface of the polystyrene aerogel layer cable, and then placed in a sealed environment at 30-40°C for 3-5h, then heated to 70-80°C for 2-3h, and finally heated to 100-120°C for 30-60min to obtain a modified aerogel layer cable; (4) The cable core coated with modified aerogel is coated and welded online with a stainless steel belt, and the stainless steel tube after welding is corrugated; A sheath layer is wrapped outside the stainless steel layer, and its raw materials include the following components by weight: 40-50 parts of chlorosulfonated polyethylene, 15-25 parts of chlorinated polyethylene, 8-16 parts of EVA, 20-30 parts of halogen-free low-smoke flame-retardant polyolefin, 1-2 parts of vinyl triethoxysilane, and 1-2 parts of silane coupling agent.
2. A fire-resistant and flame-retardant cable according to claim 1, characterized in that: The size of the organic bentonite in step (1) is 20-200 mesh.
3. A fire-resistant and flame-retardant cable according to claim 1, characterized in that: In the step (2), the weight ratio of the air-dried low-crosslinked polystyrene, tetrabutyl titanate, dichloromethane and carbon tetrachloride is 10-16:1:20:
50.
4. A fire-resistant and flame-retardant cable according to claim 1, characterized in that: In the step (3), the weight proportions of alumina trihydrate, organic composite bentonite, polydopamine, vinyltriethoxysilane and benzyl alcohol are 10-20 parts, 5-13 parts, 5-11 parts, 2-4 parts and 15-35 parts respectively.
5. The fire-resistant and flame-retardant cable according to claim 1, characterized in that: In the step (3), the weight ratio of the filler to the polystyrene aerogel is 0.5-1:
1.
6. The fire-resistant and flame-retardant cable according to claim 1, characterized in that: The silane coupling agent in step (4) is silane coupling agent KH550.
7. The fire-resistant and flame-retardant cable according to claim 1, characterized in that: The stainless steel strip in step (4) is made by welding and corrugating a stainless steel strip with a thickness of 0.1-0.2 mm, a tensile strength of 520-595 MPa, and an elongation of 42%-48%. During welding, a mixed gas of helium and argon with a volume ratio of 1:2 is used for protection. The minimum bending radius of the cable obtained is 7-15 times the diameter of the cable.
Citation Information
Patent Citations
Flame-retarding cable material based on modified bentonite and preparation method thereof
CN106046628A
Heat-insulation fireproof cable and manufacturing method thereof
CN106298019A